The social response to the measures taken to confront COVID-19 in Camagüey - Norbis Diaz Campos; María Elena Macías Llanes; Leimis Reyes Vasconcelos (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Introduction. The investigation pursues the objective of determining the social response to the measures taken to confront COVID-19 in the province of Camagüey. Classified as research-development of the Center for the Development of Social and Humanistic Sciences in Health, it was carried out in the period from April - July 2020. Material and methods. The assisted questionnaire was used to collect information on the social response to the disease. It was applied in unison in the territory in the period from May 5 to June 30, when Camagüey had not yet passed to the first recovery phase, the criterion was to assign quotas to cover all the municipalities of the province and apply in the population randomly. Based on the measures taken of social isolation, the active research of the students and professors of the University of Medical Sciences was used to collect information. The final sample was made up of 603 people surveyed. Results. The surveyed population valued the effort and political will and considered the response to the confrontation of the disease adequate, the actions of the various institutions in the confrontation with COVID-19 were also considered adequate. Discussion. It is significant that the subjects who participated in the study recognized problems with compliance with isolation and social responsibility, with the equitable distribution of resources and the need to strengthen social control measures in the face of social indiscipline.